Neonatal mortality in the case of Felege Hiwot referral hospital, Bahir Dar, Amhara Regional State, North West Ethiopia 2016: a one year retrospective chart review - Tilahun Tewabe; Yenatfanta Mehariw; Eyerusalem Negatie; Bertukan Yibeltal (BMC, 2018)
Abstract Background Ethiopia is among the countries with the highest neonatal mortality with the rate of 37 deaths per 1000 live births. In spite of many efforts by the government and other partners, non significant decline has been achieved over the last 15 years. Thus, identifying the prevalence and associated factors of neonatal mortality is very crucial for policy and program improvement. This study was designed to assess neonatal mortality rate in Felege Hiwot referral hospital, North West Ethiopia. Methods A hospital based chart review was done in Felege Hiwot referral hospital based on patient charts from July 2015 to June 2016. The data were collected using structured checklists. The collected data was coded, filtered and entered in to Microsoft Excel 2007 and transferred to STATA version 12.0 for analysis. Binary logistic regression analysis was used to identify factors associated with neonatal mortality. A p - value of < 0.05 was considered as significant. Results The prevalence of neonatal mortality in Felege Hiwot referral hospital was 13.29% (95% CI: 10.09-17.07). Early age of the newborn (< 7 days) [AOR = 0.39 (0.16-0.97)], gestational age at delivery [AOR = 2.14 (1.0-4.52)], late initiation of breastfeeding [AOR = 2.89 (0.99-8.38)], non exclusive breastfeeding [AOR = 6.77 (3.04-15.07)], inadequate ante natal visit [AOR = 5.02 (1.02-24.70)] were the determinant factors for neonatal death. Conclusions This study revealed that neonatal mortality is still high in the study area. Early age of the newborn, late initiation of breastfeeding, exclusive breastfeeding and ante natal vist were the determinant factors for neonatal mortality in the study area. Therefore, giving attention for newborns who are small for age, timely initiation of breastfeeding, exclusive breastfeeding and increasing ante natal visit were recommended to reduce neonatal mortality.